The development of an integrated management system in the personal care products industry. - Wilkie, Kieren (Stellenbosch : University of Stellenbosch, 2008)
More and more companies are realising the benefits of implementing management systems, integration of these systems would lead to a more efficient and effective management system. Environmental, quality, health and safety management systems are discussed as well as how each is implemented independently. Where the systems overlap or have common goals, in order to avoid duplication and unnecessary extra work, the development and implementation as an integrated management system (IMS) is essential and forms the major part of this project. A long term plan to implement the IMS is developed and will be implemented in this company through stages. A holistic approach is being used to improve not only the effluent but also the process and raw materials. The company being focussed on is broken down into different sections and each section carefully investigated to find possible process improvements. The company is looking to become as automated as possible to reduce human error, but due to financial concerns, everything is to be done as economically as possible, or over a longer time span. The company is looking to implement an environmental management system (EMS) to become ISO 14000 certified and a quality management system (QMS) to become ISO 9000 certified as this would: • improve product marketing, • minimise long term costs, • ensure the future development of the company, and • help give the company an edge in the highly competitive market. A brief background of the organisation is given in order to determine the current (pre-implementation) status of the company. The EMS, QMS and Operational Health and Safety are discussed as well as how each is implemented independently. A gap analysis of each of the management systems is carried out and where the systems overlap or have common goals, these systems are integrated. The different functional departments of the organisation nl. inventory, production and administration are investigated and suggestions on how to improve these are documented. These suggestions are to be carried out first as these are the most obvious and currently cause the most problems. Once these problems are fixed, the gap analysis of each system is to be looked at and implemented. The water use of the organisation is investigated and some practical ways of decreasing the water use are suggested. Different ways of treating the effluent is discussed and it is decided that the best setup would be two tanks in series, including a flow equalisation tank and a chemical neutralisation tank. Depending on the pilot plant investigation an extra tank can be used to improve the water quality. One of the fundamental foundations to an effective and efficient management system is management commitment and the management at AIC are not committed enough. Employees should be motivated through fair pay, training and recognition as this will reduce human error and also improve the general feeling in the organisation. The IMS will be greatly enhanced if business ethics and social responsibilities are incorporated. Training seems to be the major problem in the organisation at present and once the appropriate sections of the IMS have been completed, training should become part of the company’s routine.